Analisis Indeks Kepuasan Masyarakat Studi Kasus: Puskesmas Pananae Kota Bima - Nurfaridah, Nurfaridah; Saimi, Saimi; Karjono, Karjono; Abdul Khalik, Lalu (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the factors influencing the interest in injectable contraceptives in Bima City. The research used a quantitative analytic method with a cross-sectional approach. The sample consisted of 95 women of reproductive age who used injectable contraceptives. Data were analyzed using Chi-Square and logistic regression tests to determine the relationships and effects among variables. The results showed that knowledge, husband’s support, and the role of health workers had significant effects on the interest in injectable contraceptives. Meanwhile, attitude and media information showed no significant influence. The study concludes that interest in injectable contraceptives is strongly influenced by women's knowledge and husband’s support, and further supported by the active role of health workers. Increased education and communication by health personnel are needed to raise public awareness